Qué es en realidad una politica pública en Colombia (2011)
Despite the complexity of the design and implementation of public policies, these policies are implemented in Colombia by governments, basically using two tools: the laws and the development plans, where we see that at least in Colombia, the practice of public politics is one issue of short-term, where to solve the immediate is imperative, while to understand and to practice them, just misunderstood as a command-obedience relationship, based on clientelism, where few manage, others obey and suffer many more. Our political system colombian wasn`t only heritage of our conquerors, but was weaving a web of complexities that favored only those in power, while most (mis) used to the normality and perverse unequal. To provide clarity, this paper seeks to analyze and emphasize public policies harmonized within the development plans of each government, so that readers can make a brief tour of the last 25 years in Colombia, allowing them to have a useful and simple tool for addressing and analyzing the evolution of these policies